Kontribusi PT Pertamina Geothermal Energy Terhadap Kondisi Sosial Keagamaan Masyarakat Kecamatan Ulubelu Kabupaten Tanggamus - Anggraeini, Rina (Socio Religia, 2022)
The State-Owned Coorporate (BUMN) PT Pertamina is one of the companies that utilizes the potentials number of regions in Indonesia. PT Pertamina Geothermal Energy utilizes geothermal energy to be used as a power plant located in Lampung, precisely in Ulubelu sub-district, Tanggamus district which has officially started operating since 2012. The contribution given by PT Pertamina Geothermal Energy is Corporate Social Responsibility (CSR), direct and indirect assistance. The contribution of PT Pertamina Geothermal Energy has also penetrated the religious sector which has a positive impact on the people of Ulubelu District, Tanggamus Regency. This article discusses the socio-religious conditions of the people in the Ulubelu sub-district, Tanggamus Regency and wants to know the contribution of PT Pertamina Geothermal Energy to the socio- religious condition of the Ulubelu sub-district, Tanggamus Regency. This qualitative research uses a sociologicalapproach with interviews, observations and documentation as data collection methods. The results showed that the socio-religious conditions of the people of Ulubelu District, Tanggamus Regency were quite good at practicing religious teachings with high religious awareness seen from how the community carried out religious activities and in practicing religious teachings and PT Pertamina Geothermal Energy contributed to the socio-religious conditions of the Ulubelu District community through Corporate Social Responsibilities (CSR), direct and indirect assistance, infrastructure development, namely raising religious awareness for the people of Ulubelu District, increasing the worship of the people of Ulubelu District, strengthening social relations and community solidarity in Ulubelu District, Tanggamus Regency.